PENGGUNAAN GADGET DAN KEPRIBADIAN PENGGUNANYA DI SMP N 3 PEKANBARU - Admar, Hidayati; Yakub, Elni; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The use of gadget aiready is the phenomena of the usual among students. A variety of the impact of the presence of gadget started can be feit. Indirectcy this will lead to change the patters of life of routine human and inferaction in a society where they lived, is not an exception far students such as using gadget to access the aducts. And it’s the use of gadget until late at night resucted in the students sleepy in class while learning. This study aims to find out picture of the us of gadget and personality users. The students said users gadget in this study is if in a day. The subject in this study is the students who use gadget as many twenty seven people with purposive sampling. In this study instrument used is inguiries. The results of the study found a average of students use gadget at home after going home from school, in a almost entirely playing gadgrt 4 until 6 hours a day, the kind of gadget must often used is smartphone. Most students use gadget for social media. The impact that is felt students due to use gadget too long is sick irritation eyes. While on aspects of the personality of students who use gadget almost entirely having a personality of healthy like respect for the old manKey Words: Gadget, Personality